PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA MERLYNN PARK HOTEL DI JAKARTA PUSAT) - Katim, Katim; Wiliyawati, Cucu (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
The purpose of this paper is to examine the influence of transactional leadership style and motivation on employee performance. The methodology used is survey based. Primary data were collected from 40 employees of Merlynn Park Hotel in Jakarta. Data analysis using simple and multiple linear regression to test the hypothesis. The research resulted in mixed ï¬ndings that only partially effect of motivation on performance. No signiï¬cant relationship was found between transactional leadership and performance. Simultaneously, transactional leadership style and motivation no significant effect on performance. Keywords: transactional leadership, motivation